2012
DOI: 10.7205/milmed-d-11-00161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermotherapy for the Treatment of Cutaneous Leishmaniasis in Kabul, Afghanistan: A Randomized Controlled Trial

Abstract: Anthroponotic cutaneous leishmaniasis (CL) is a common cause of ulcerative lesions and disfiguring scarring among children in Afghanistan. Most lesions occur on the face and are commonly caused by the trypanosome protozoan parasite Leishmania tropica, transmitted by the bite of an infected sandfly (Phlebotomus sergenti). This study compared the effectiveness of a single localized treatment with thermotherapy to 5 days of intralesional administration of Glucantime for the treatment of CL. Three hundred and eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 14 publications
0
28
1
Order By: Relevance
“…Considering the known tissue-regenerative activity of pharmaceutical NaClO 2 [35][39], [65][67] and its cytotoxicity against extra- and intracellular L. tropica parasites (reported here), it was unexpected to see that the therapeutic benefit of including DAC N-055 in the EC/MWT protocol was confined to a subgroup of patients with a persistently high parasite loads in the 2 nd biopsy and to the partial prevention of relapses. A plausible explanation is that EC/MWT alone already exerted a strong anti-parasitic and wound healing effect, which in most patients could not be further enhanced by the addition of DAC N-055.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Considering the known tissue-regenerative activity of pharmaceutical NaClO 2 [35][39], [65][67] and its cytotoxicity against extra- and intracellular L. tropica parasites (reported here), it was unexpected to see that the therapeutic benefit of including DAC N-055 in the EC/MWT protocol was confined to a subgroup of patients with a persistently high parasite loads in the 2 nd biopsy and to the partial prevention of relapses. A plausible explanation is that EC/MWT alone already exerted a strong anti-parasitic and wound healing effect, which in most patients could not be further enhanced by the addition of DAC N-055.…”
Section: Discussionmentioning
confidence: 79%
“…Presumably, it had two major effects: it caused a reduction of the parasite load, due to the coagulation and physical removal of tissue by heating the lesions with a high-frequency current; and it created a fresh wound bed for subsequent granulation and epithelialization. Unlike to the radio-frequency-induced heat therapy (50°C), which also proved effective in endemic areas such as Iran and Afghanistan [15], [19], [65], the sensitivity of Leishmania parasites to temperatures above 39°C is not the primary mechanism of action of our EC approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…180 Another recent study from Afghanistan showed that single localized treatment with thermotherapy was more effective than 5 days of intralesional administration of Glucantime (82.5%vs 74%). 181 It was also seen to have similar albeit low efficacy as SSG for skin lesions caused by L. major (48% vs 54%). 182 In another study from Iran, thermotherapy once weekly for 4 weeks had a cure rate of 80.7 % compared to 55.3 % with intralesional antimonials.…”
Section: Review Of Antileishmanial Agentsmentioning
confidence: 91%
“…According to Murray and Lopez study on global burden of disease, we applied a disability weight of 0.023 due to CL. [171920] Disability duration, i.e., the time a patient lives with the disability due to the disease, was estimated at 0.25 years or 3 months. [111617] To calculate DALYs, incidence rate in target population in a given year was multiplied by disability duration and disability weight.…”
Section: Methodsmentioning
confidence: 99%